Understanding Digital Governance Practices: The Importance of the Coretax System in Advancing Digital Tax Reform in Indonesia - Agusniar Rizka Luthfia; Eka Nada Shofa Alkhajar (International Journal of Social Science and Humanity, 2026)
Coretax (Core Tax Administration System) is an information technology–based tax administration system developed by the Directorate General of Taxes (DGT) of Indonesia. This study examines the implementation of the coretax system as one of the government’s efforts to reduce tax leakage by optimizing the existing tax database. This research employs a qualitative method with a literature-based approach. The findings reveal that the coretax system is indeed necessary to be implemented and developed as the foundation of digital tax reform. However, it is important to note that the success of digitalization depends not only on the quality of the platform, but also on the readiness of human resources, infrastructure, and a supportive environment. Therefore, the implementation of coretax needs to be adapted to the conditions of different regions across Indonesia. It should be introduced gradually and piloted in selected areas, accompanied by extensive dissemination and public education regarding the coretax system through both offline and online channels to ensure that the objectives of system reform can be achieved. Internally, the government must strengthen the digital competencies of state apparatuses, take an active role in auditing, integrating, and mitigating the coretax system, and promote system interoperability. In this way, coretax can become a significant testing ground for Indonesia’s digital sovereignty.